1999
DOI: 10.1007/bf02884836
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions and acute physiological responses to stress

Abstract: One pathway through which stressors are thought to influence physiology is through their effects on emotion. We used metaanalytic statistical techniques with data from nine studies to test the effects of acute laboratory stressors ( speech, star mirror-image tracing, hand grip) on emotional (undifferentiated negative emotion, angel; anxiety) and cardiovascular (CV) response. In all of the studies, participants responded to stressors with both increased CV response and increased negative emotion. Increases in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 44 publications
8
92
0
1
Order By: Relevance
“…Finally, on the basis of recommendations from a recent review of the literature on perceived racism and cardiovascular reactivity (13), we explored whether psychological distress in response to the stressors mediated racial differences in cardiovascular reactivity to the different social stressors. Both theoretical models and empirical evidence suggest that negative emotions may play a role in cardiovascular reactivity (19).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, on the basis of recommendations from a recent review of the literature on perceived racism and cardiovascular reactivity (13), we explored whether psychological distress in response to the stressors mediated racial differences in cardiovascular reactivity to the different social stressors. Both theoretical models and empirical evidence suggest that negative emotions may play a role in cardiovascular reactivity (19).…”
Section: Hypothesesmentioning
confidence: 99%
“…We used a design in which all participants were exposed to identical stimuli to avoid confounds associated with using different stimuli for different groups. In addition, the study included a control speaking condition to adjust for the effects of speaking on reactivity (17)(18)(19), presented the speech tasks in counterbalanced order, and included measures of cardiovascular reactivity to the stressors as well as recovery following the stressors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pain catastrophizing is associated with elevated negative affect (Hirsh et al 2007), which in turn is often associated with heightened cardiovascular stress reactivity (Burns 1995;Feldman et al 1999;Kamarck et al 1998;Prkachin et al 1999). Prior work indicates that elevations in systolic blood pressure trigger endogenous analgesic mechanisms through functional links between the cardiovascular and pain regulatory systems (e.g., Bruehl and Chung 2004;Edwards et al 2001Edwards et al , 2003Ghione 1996;Rau and Elbert 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental manipulations often increase self-reported negative affect (e.g., the experience of anger) and influence physiological responses (e.g., raise blood pressure [BP]), the relationship between the changes in affect and physiology is often statistically nonsignificant or modest in magnitude. For example, a meta-analysis indicated that changes in negative affect due to a stressor only accounted for 2-12% of changes in cardiovascular responses despite large changes in cardiovascular responses after the stressor (Feldman et al, 1999). If participants report more negative affect as a result of a stressor, and their bodies react to the same stressor, then one would reasonably expect that the changes in affect and physiology would be strongly associated.…”
mentioning
confidence: 99%